(untitled) (Fiep Bulletin - online, 2013)
Investigate the indices of the functional capacity on a comparative evaluation of elderly who practice some modality of physical exercises in a Social Project of Dourados/MS. The field study, having a transversal character, quantitative-descriptive, through the application of 800 meters of walking tests, sitting down and standing up of the chair and climbing steps, with evaluation of 36 people, being 95% female (n=34) and 5% male (n=2), with ages between 60 to 72, in 03 modalities of physical activity of the Social Project: Water Aerobics, Gymnastics and Dance, all of them having 12 people of each sample, through drawing among the regulars of each modality. In the Water Aerobics it was obtained an average of 599 seconds in the 800 meters of walking test; 57 seconds in the sitting and standing test; and, 51 centimeters for the climbing steps. In the Gymnastics, the average was 583 seconds in the 800 meters of walking test; 65 seconds in the sitting and standing test; and, 48 centimeters to climb steps. In the Dance, it was obtained an average of 604 seconds in the 800 meters of walking test; 57 seconds in the sitting and standing test; and 48 centimeters for the climbing steps test. It was concluded through the results that the elderly who practice regular physical exercises improve their functional capacity making easier their everyday activities, indication that can be useful for new studies.